Balancing stability and function: impact of the surface charge of SARS-CoV-2 Omicron spike protein - Daniel Lauster; Rainer Haag; Matthias Ballauff; Andreas Herrmann (npj Viruses)
Abstract The ectodomain of the Omicron SARS-CoV-2 spike has an increased positive surface charge, favoring binding to the host cell surface, but may affect the stability of the ectodomain. Thermal stability studies identified two transitions associated with the flexibility of the receptor binding domain and the unfolding of the whole ectodomain, respectively. Despite destabilizing effects of some mutations, compensatory mutations maintain ECD stability and functional advantages thus supporting viral fitness.